Avaliação do perfi de mutações e resistência aos inibidores de transcriptase reversa e protease em variantes HIV presentes em pacientes coinfectados pleo VHC - Cruz, Andressa Alves de Almeida [UNESP] (2014)
HIV/HCV coinfection has become an important public health problem due to the possibility of these viruses act synergistically, which can accelerate the progression of liver disease related to HCV and may favor the spread of HIV. It is established that the high genetic variability of HIV generates mutations, giving the virus the ability to respond quickly to changes in selective pressure exerted by the immune system or by antiretroviral therapy (ART). It is not known whether the presence of HCV can promote the emergence of resistant variants of HIV. Thus, this study aimed to evaluate the profile of resistance mutations to classes of reverse transcriptase inhibitors: nucleoside and nucleotide analogue Reverse Transcriptase Inhibitors (NRTIs), non-nucleoside analogue Reverse Transcriptase Inhibitors (NNRTIs) and protease inhibitors (PIs), in circulating HIV variants in HCV coinfected individuals. In this study were included 19 HIV/HCV coinfected patients, over 18, with plasma HIV viral load of at least 1,000 RNA copies/mL. These patients were treated at the Ambulatory of Gastroenterology of the Faculty of Medicine of Botucatu and at the Day-Hospital “Domingos Alves Meira”. Genotyping and sequencing were performed at the Laboratory of Molecular Biology of the Blood Center of Botucatu, Faculty of Medicine, UNESP, using the Trugene HIV-1 Genotyping Kit (Siemens HealthcareDiagnóstics, Inc. Tarrytown, NY, USA). Two subtypes of HIV-1, B and F, were observed, but the subtype B was observed more often, 94.74%. It was observed HCV genotypes 1 (94.74%) and 3 (5.26%). All patients presented resistance mutations to the evaluated classes, and the mutations associated to NRTIs as M184V were observed more often (57.89%). The most common mutations associated to NNRTIs were K103N and G190A, present in 21.05% of the samples. The main mutations associated to IPs more frequent were M46I, I54V and V82A, with 15.78% ...